KANDUNGAN FENOLIK DAN AKTIFIVATS ANTIOKSIDAN EKSTRAK KULIT ARI KENARI (Canarium vulgare Sp.) - Djasibani, Hemy R.; Djarkasi, G.S. Suhartati; Suryanto, Edi (Jurnal Ilmu dan Teknologi Pangan, 2013)
Canary is original plants Indonesia which growing many in Indonesia area part of east, like North Sulawesi, Maluku, Seram and Alor island. This study aims to determine the total conten of phenolic compounds and antioxidant activity of extracts of canary husk of some species of Canarium vulgare Sp. solvent is hexane, ethanol, ethyl acetate and acetone. Results showed that the canary husk extract of Canarium vulgare Sp. species has a total phenolic content and antioxidant activity are great. Highest total phenolic content of the extract produced by solvent acetone was 171.0 mg/kg, followed by extracts of ethyl acetate, ethanol, and hexane has a total phenolic content of consecutive 111,17 mgkg, 99,67 mg/kg, and 67,17 mg/kg and the highest antioxidant activity in the solvent ethyl acetate extract of 93.66% followed by 92.97% acetone extract, ethanol amounted to 89.92% and by 14.45% hexane. Result of this research indicate that canary husk acetone extract have fenolik content and highest antioxidant.